Keteladanan Guru sebagai Strategi Penguatan Perkembangan Sosial-Emosional Anak Usia Dini di PAUD Al Barkah Rengasdengklok - Deden Deni Mahendra; Yanti Apriani; Latipah; Siti Karmila; Daresih; Yulia Ayu Rahmatul Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Social-emotional development in early childhood is an important aspect in shaping children’s behavior and personality that requires attention from an early age. Early childhood education environments play a strategic role in facilitating this development, particularly through teachers’ role modeling in daily interactions. This study aims to describe teacher role modeling as a strategy for strengthening the social-emotional development of early childhood learners at PAUD Al Barkah Rengasdengklok. The study employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation involving teachers and early childhood learners as research subjects. The findings indicate that teacher role modeling is reflected in polite communication, calm emotional regulation, consistent discipline, and guidance provided to children in resolving conflicts. Children demonstrated improvements in emotional regulation, social interaction, and responsibility through processes of observation and imitation of teachers’ behavior. Teacher role modeling creates a safe learning environment that supports children’s social-emotional development. The conclusion of this study indicates that teacher role modeling contributes to strengthening early childhood social-emotional development through everyday practices in the school environment. Keywords: teacher role modeling, social-emotional development, early childhood